Oxybutynin vs Placebo for Hot Flashes in Women With or Without Breast Cancer: A Randomized, Double-Blind Clinical Trial (ACCRU SC-1603). Issue 1 (21st October 2019) - Leon-Ferre, Roberto A; Novotny, Paul J; Wolfe, Eric G; Faubion, Stephanie S; Ruddy, Kathryn J; Flora, Daniel; Dakhil, Christopher S R; Rowland, Kendrith M; Graham, Mark L; Le-Lindqwister, Nguyet; Smith, Thomas J; Loprinzi, Charles L
Abstract: Background: Hot flashes (HFs) negatively affect quality of life among perimenopausal and postmenopausal women. This study investigated the efficacy of oxybutynin vs placebo in decreasing HFs. Methods: In this randomized, multicenter, double-blind study, women with and without breast cancer with 28 or more HFs per week, lasting longer than 30 days, who were not candidates for estrogen-based therapy, were assigned to oral oxybutynin (2.5 mg twice a day or 5 mg twice a day) or placebo for 6 weeks. The primary endpoint was the intrapatient change from baseline in weekly HF score between each oxybutynin dose and placebo using a repeated-measures mixed model. Secondary endpoints included changes in weekly HF frequency, HF-related daily interference scale questionnaires, and self-reported symptoms. Results: We enrolled 150 women. Baseline characteristics were well balanced. Mean (SD) age was 57 (8.2) years. Two-thirds (65%) were taking tamoxifen or an aromatase inhibitor. Patients on both oxybutynin doses reported greater reductions in the weekly HF score (5 mg twice a day: −16.9 [SD 15.6], 2.5 mg twice a day: −10.6 [SD 7.7]), placebo −5.7 (SD 10.2); P  < .005 for both oxybutynin doses vs placebo), HF frequency (5 mg twice a day: −7.5 [SD 6.6], 2.5 mg twice a day: −4.8 [SD 3.2], placebo: −2.6 [SD 4.3]; P  < .003 for both oxybutynin doses vs placebo), and improvement in most HF-related daily interference scale measures and in overall quality of life. Patients on both oxybutynin arms reported more side effects than patients on placebo, particularly dry mouth, difficulty urinating, and abdominal pain. Most side effects were grade 1 or 2. There were no differences in study discontinuation because of adverse effects. Conclusion: Oxybutynin is an effective and relatively well-tolerated treatment option for women with HFs.